Strategi Penanganan Pelecehan Seksual di Kalangan Remaja: Tinjauan Literatur - Fino Ardiansyah; Matsna Wilda Muqorona; Fariskha Yulfa Nurahma; Muhammad Dodik Prasityo (Jurnal Keperawatan Klinis dan Komunitas (Clinical and Community Nursing Journal), 2023)
Background: There are many sexual violence cases take place from school to college. Women mostly become sexual harassment victims, while men largely become the perpetrators. The most common forms of sexual harassment include hurtful or threatening comments, direct aggressive act, and online sexual harassment. Sexual harassment causes health problems, damaging mental, physical, social condition, and somatic effect. Eventhough, various efforts have been done, sexual harassment case against women keeps increasing.Objective: To explore strategies for handling sexual harassment in adolescents.Method: The research used Sexual AND Harassment as the keywords. Literature was selected from ScienceDirect, PubMed, ClinicalKey, and ProQuest databases with screening results 21,311 (N) articles. Total 5 (n) articles were analyzed from the results of the research quality assessment process at the minimum quartile of Scimago Journal Rank (SJR) 1 (Q1) and they also analyzed using critical appraisalÂ  from Joanna Briggs Institute.Result: There were five literatures that fulfilled the criteria and had the strategy in reducing and preventing the occurrence of sexual harassment as their content. Themes of these articles included i.e.: prevention of sexual harassment (n=1), education material in sexual harassment content (n=1), and sexual harassment intervention (n=3).Conclusion: These three strategies (sexual harassment prevention, education, and intervention) can be applied in schools or colleges and can be used as a curriculum to improve individual behavior and reduce harassment.ABSTRAKLatar belakang: Banyak kasus kekerasan seksual terjadi di sekolah hingga perguruan tinggi. Pada umumnya, korban pelecehan seksual adalah perempuan dan pelaku pelecehan seksual sebagian besar adalah laki-lakiÂ . Bentuk pelecehan yang paling besar, meliputi: komentar yang menyinggung atau mengancam; perlakuan secara langsung; serta pelecehan seksual di dunia maya (online). Pelecehan seksual mengakibatkan masalah kesehatan, dapat merusak kondisi mental, fisik, sosial, hingga menimbulkan efek somatik. Berbagai upaya penanganan kasus kekerasan seksual telah dilakukan. Namun, kasus kekerasan terhadap perempuan masih mengalami peningkatan.Tujuan: Mengkaji strategi penanganan pelecehan seksual pada remaja.Metode: Penelusuran menggunakan kata kunci Â untuk mengidentifikasi penelitian yang relevan. Seleksi literatur dilakukan melalui database yang tersedia di ScienceDirect, PubMed, ClinicalKey, dan ProQuest, dengan hasil skrining sebanyak n = 21.311 artikel. Total (n=5) artikel dianalisis dari hasil proses penilaian kualitas penelitian pada kuartil minimal Scimago Journal Rank (SJR) 1 (Q1) dan studi yang dianalisis dilakukan Critical Appraisal menggunakan Joanna Briggs Institute.Hasil: Lima literatur yang telah diperoleh, memiliki tema â€œStrategi dalam Mengurangi dan Mencegah Terjadinya Pelecehan Seksual.â€ Tema-tema tersebut membahas di antaranya: pencegahan pelecehan seksual (n=1); pendidikan pelecehan seksual (n=1); dan intervensi pelecehan seksual (n=3).Simpulan: Ketiga strategi ini (pencegahan, pendidikan, dan intervensi pelecehan seksual) dapat diterapkan di sekolah atau perguruan tinggi dan dapat digunakan sebagai kurikulum untuk meningkatkan perilaku individu dan mengurangi kekerasan.